2020
DOI: 10.3390/pr8111351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pasteurisation on Methane Yield from Food Waste and Other Substrates in Anaerobic Digestion

Abstract: The effect of pasteurisation and co-pasteurisation on biochemical methane potential values in anaerobic digestion (AD) was studied. Pasteurisation prior to digestion in a biogas plant is a common hygienisation method for organic materials which contain or have been in contact with animal by-products. Tests were carried out on food waste, slaughterhouse waste, animal blood, cattle slurry, potato waste, card packaging and the organic fraction of municipal solid waste (OFMSW); pasteurisation at 70 °C for 1 h was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The adaptation of IC engines to combustion of gaseous fuels may become a contemporary scientific trend as to the use of biogas [90][91][92]. Biogas obtained from the decomposition of, e.g., sewage [93], organic municipal waste [94,95], animal faeces [96], agricultural and food industry waste [97,98] and plant materials [96,97,99], can be used by plants processing these materials to propel their machinery and equipment [100,101]. Biogas is a mixture of gases characterized by a varied composition, but it can be purified to bio-methane and then meet the quality standards of natural gas [102].…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation of IC engines to combustion of gaseous fuels may become a contemporary scientific trend as to the use of biogas [90][91][92]. Biogas obtained from the decomposition of, e.g., sewage [93], organic municipal waste [94,95], animal faeces [96], agricultural and food industry waste [97,98] and plant materials [96,97,99], can be used by plants processing these materials to propel their machinery and equipment [100,101]. Biogas is a mixture of gases characterized by a varied composition, but it can be purified to bio-methane and then meet the quality standards of natural gas [102].…”
Section: Discussionmentioning
confidence: 99%
“…This can be as short as 50 days for substances such as cellulose [23] or may take 100 days or more for some cropbased materials due to their lignocellulosic content [32]. In a recent attempt to standardise BMP tests, it is recommended that the test is terminated when the daily net methane production during three consecutive days is less than 1% of the accumulated methane produced from the substrate already [24,31], although the duration of the test should also be taken into consideration for unexpected degradation patterns or inhibition effects [33]. The inoculum must necessarily be digested separately (under the same conditions) to obtain a control value (amount of methane produced by the inoculum only); this control value must be deducted from the results of the test vessels to obtain the yield attributed to the actual test substrate.…”
Section: Methane Potentials Obtained In Bmp and Long Retention Batch Testsmentioning
confidence: 99%
“…Pasteurization is traditionally used to suppress microbial activity, which is why it might be useful in suppressing CH 4 emissions. Zhang et al (2020) further showed that pasteurization can increase the CH 4 yield of some specific substrates during anaerobic digestion. Furthermore, it can relatively easily be applied on pig farms or in biogas plants, especially if coupled with a manure heat exchanger system, as described in two pending patents (Henriksen et al, 2021a;2021b).…”
mentioning
confidence: 95%